Development of an electric screwdriver with incorporated torque measuring device - Okiy, Stanley; Emagbetere, Eyere.; U. Oreko, Benjamin (International Journal of Engineering and Technology, 2018)
The use of manual screwdriver is labor intensive and time consuming in some specific engineering work. Information on driving torques of screwdrivers for some common building materials is sparse, despite its relevance. In this work, a portable electric powered screwdriver with an incorporated torque measuring device was developed and then used to assess the driving torques of a locally made brick, Rubber wood and Abura wood. A black phosphate flat-head Phillips slotted screw, Phillips pan head brass coated screws, Phillips hexagonal head with washer brass coated and a Steel sheet metal screw combination Phillips-slotted drive were selected for the investigations. The screwdriver was used to access the drive torques for the selected materials. From the result, it was observed that the driving torque was not significantly affected by the type of material, screw type and screw size. However, the effect of the type of screw head on drive torques was significant.Â